2008
DOI: 10.1039/b715584k
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium catalysed dehydrogenative borylation of alkenes: Vinylboronates via C–H activation

Abstract: We present herein a high yield, highly selective catalytic synthesis of vinylboronate esters (VBEs), including 1,1-disubstituted VBEs, from alkenes without significant hydrogenation or hydroboration, using the simple catalyst precursor, trans-[RhCl(CO)(PPh3)2] (1), and the diboron reagents B2pin2 (2a, pin = pinacolato = OCMe2CMe2O) or B2neop2 (2b, neop = neopentylglycolato = OCH2CMe2CH2O), or the monoboron reagent HBpin, all of which are commercially available. The reactions were conducted at 80 degrees C usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 81 publications
1
59
1
Order By: Relevance
“…50,52,6669 To address this question, we examined pathway II , which differs from the family of mechanisms described under pathway I in that pathway II involves the migratory insertion of the coordinated alkene into the Rh–B bond. 7072 To accommodate the desired migratory insertion, pinBH adds to Im0 in a direction more perpendicular (rather than parallel, as previously examined) to the coordination plane encompassing Rh (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…50,52,6669 To address this question, we examined pathway II , which differs from the family of mechanisms described under pathway I in that pathway II involves the migratory insertion of the coordinated alkene into the Rh–B bond. 7072 To accommodate the desired migratory insertion, pinBH adds to Im0 in a direction more perpendicular (rather than parallel, as previously examined) to the coordination plane encompassing Rh (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…14 A more selective palladium-catalyzed method has since been described but is restricted to terminal alkenes bearing electronically activating groups such as aryl and alkenyl substituents (Scheme 2A). 15 …”
Section: Introductionmentioning
confidence: 99%
“…[1] Avariety of transition-metal complexes such as rhodium(I), [2] iridium(I), [3] ruthenium(II), [4] iron(0), [5] and cobalt(I) [6] catalyze the hydroboration of terminal alkenes with pinacolborane (HBpin), thus forming alkyl pinacolboronates in ar egioselective way [ Figure 1a]. [10,11] Herein, we report ar hodium(I)-catalyzed reaction of aliphatic terminal alkenes with HBpin, which preferentially produce dehydrogenative borylation compounds (Figure 1b). [7][8][9] For example,M asuda et al reported that the reaction of styrene with HBpin in the presence of neutral [RhCl(cod)] 2 gave the dehydrogenative borylation product along with as mall amount of the hydroboration products.…”
mentioning
confidence: 99%